2021
DOI: 10.1111/aji.13497
|View full text |Cite
|
Sign up to set email alerts
|

Using principal component analysis to examine associations of early pregnancy inflammatory biomarker profiles and adverse birth outcomes

Abstract: Objective: Inflammation as a risk factor for preterm birth is well-established. The primary objective of this analysis was to examine whether individual cytokines versus a composite indicator of mid-pregnancy inflammation are significantly associated with risk for adverse birth outcomes. Study design:A multi-site prospective study was conducted in a socio-demographically diverse cohort of 610 pregnant participants. At a study visit between 12 and 20 6/7 weeks' gestation, low-grade inflammation was measured via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…The most common reasons for exclusion were lack of focus on perinatal distress or the AL index ( n = 246), inappropriate study population ( n = 22), and inappropriate study design ( n = 55). Several studies (Coussons-Read et al, 2012 ; Kramer et al, 2013 ; Gillespie et al, 2021 ; Huang et al, 2021 ; Keenan-Devlin et al, 2021 , 2022 ) initially appeared promising; however, these studies did not meet all inclusion criteria and lacked connection to the AL framework as well as pathways of perinatal stress and distress, and were therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The most common reasons for exclusion were lack of focus on perinatal distress or the AL index ( n = 246), inappropriate study population ( n = 22), and inappropriate study design ( n = 55). Several studies (Coussons-Read et al, 2012 ; Kramer et al, 2013 ; Gillespie et al, 2021 ; Huang et al, 2021 ; Keenan-Devlin et al, 2021 , 2022 ) initially appeared promising; however, these studies did not meet all inclusion criteria and lacked connection to the AL framework as well as pathways of perinatal stress and distress, and were therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…This imbalance between downregulated reproductive hormones and stimulated inflammation could set in motion a cascade of molecular changes ending in preterm delivery [43]. Notably, a recent study of 610 pregnancies, found that increased IL-6 and c-reactive protein between gestational weeks 12-20 was associated with decreased gestational age and an increased odds of preterm delivery [44]. Unfortunately, the study did not consider sex-specificity; however, placental cytokine levels and responses have been shown to vary by fetal sex [45].…”
Section: Discussionmentioning
confidence: 99%
“…Angiopoietins are also present in the placenta and are involved in the inflammatory pathway through mediating angiogenesis and vascular restructuring [ 33 ]. The implementation of molecular imaging using contrast-enhanced ultrasound could help to identify at-risk pregnancies, as placental inflammation is associated with placental dysfunction and poor pregnancy outcomes [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%